The race for clinical trials on Omicron-based COVID-19 vaccine candidates: Updates from global databases - Viveiros-Rosa, Sandro G.; Mendes, Cristina DS.; Farfán-Cano, Galo G; El-Shazly, Mohamed (Narra Sains Indonesia, 2022)
The coronavirus disease 2019 (COVID-19) has caused more than 6.5 million deaths globally as of June 10, 2022. The severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2) Omicron variant (B.1.1.529) has the greatest transmission rate and can cause hospitalization in vaccinated individuals. It has been the most distinct SARS-CoV-2 variant of concern to date. The existing inactivated vaccines made with the wild-type strain are less efficient to prevent disease and/or hospitalization associated with the Omicron variant, even after a booster dose. Hence, it is crucial to develop new vaccines that are effective against this variant. The objective of this study was to summarize the data on existing clinical trials for new COVID-19 vaccines formulated against Omicron variant. Clinical trials from the international clinical trials registry platforms were searched and analyzed. As of June 10, 2022, a total of 15 clinical trials are available consisting of six and nine clinical trials of inactivated and messenger RNA (mRNA)-based vaccine candidates containing the Omicron variant, respectively. Those trials are evaluating four inactivated and four mRNA-based vaccine candidates. Although Omicron-specific vaccines are highly desired, their development is challenging since the SARS-CoV-2 variant formation is still unpredictable. Although two vaccines from Pfizer and Moderna have been approved for emergency use in the US and the UK for Omicron variant, the Asian pharmaceutical companies such as CNBG (Sinopharm), Sinovac, and Shifa Pharmed also have Phase 3 clinical trials under development and almost all clinical trials are expected to be completed in 2023. These results should help guide academics and policymakers in the COVID-19 vaccine field regarding investments in updated booster doses against the SARS-CoV-2 Omicron variant.